Estudo comparativo entre os modelos de carreira proteana e carreira sem fronteiras por meio de escalas de atitudes - Silva, Jefferson de Alcântara e (2009)
With the aim of amplifying the understanding of career management and using contributions from existing studies on career models, this work was oriented by the general objective of proving that there is a relationship between models of protean career and boundaryless career, by relating career attitude scales. A procedure of semantic validation was carried out in two research instrument already existent in the United States. After this semantic validation of the attitude questionnaires was accomplished and tested with a group of 15 people, the instruments were applied to a sample of 516 undergraduate Business Administration students from the University of Uberaba (UNIUBE), Uberaba campus, and 426 of these had their scores validated after analysis of missing data. Reliability and inner consistency test results of the adapted instruments were accomplished by using Cronbach alpha coefficient, Spearman-Brown split-half coefficient analysis and evaluation of the ground and ceiling effect of the answered items. A one-way ANOVA was also used for comparing the averages among groups segmented by periods of study, gender and profession, the survey being concluded with the correlation analysis between the scores obtained for protean and boundaryless career. Results indicated the moderate presence of attitudes that are inherent to both models of career studied, as well as pointed to a significant direct relationship between protean and boundaryless career as to the level of career attitudes in the following domains: Self-orientation, orientation by values, organizational mobility and boundaryless profile. This research opens up the possibility for other studies on career management, using the adapted and validated questionnaires in this research in conjunction with other existing instruments that may measure the inclinations of existing career profiles in students, as well as in professionals already placed in the job market.